Crypto Uncovered The Evolution of Bitcoin and the Crypto Currency Marketplace - Swammy, Sarah (Springer International Publishing, 2018)
"As Executive-in-Residence, 2018 at Cornell Tech, cryptocurrency is an area in which I've had minimal exposure, and needed to become more fluent with a baseline understanding of its technologies and ideology. As a representative of industry professionals with deep expertise in talent strategy inclusion, diversity, and equality practices, we have a vested interest in the future, assuring we are doing our best to encourage the next generation of technology leaders and thought leaders to leave no individuals, no groups, and no communities behind in new opportunities for wealth creation, access, and economic independence. The authors, Sarah Swammy, Richard Thompson, and Marvin Loh, adeptly demonstrate their experiential subject matter expertise as well as offer a clear picture of interdependency with our existing monetary infrastructure. This book will greatly benefit readers who desire neutral and objective insight into this new era, and who share the desire to extend all roads leading to economic equality." -Denise Young Smith, Executive-in-Residence, 2018, Cornell Tech "Cryptocurrency and blockchain enterprise platforms have the potential to transform commerce and the value chain in both for-profit and non-profit sectors. However, not all communities are aware of this potential and how they can benefit from this transformation. At the UNCF, we are deeply concerned about and committed to increasing the value proposition for historically black colleges and universities (HBCUs) in the new economy, and how our faculty and students cannot just be passengers but drive the development of next-generation technologies including blockchain platforms. We applaud the authors Richard Thompson,Sarah Swammy, and Marvin Loh in their attempts to illuminate how cryptocurrency and blockchain platforms actually work and their implications for the future economy. This is important work that will help diverse communities such as HBCUs lead in the development of these technologies to build wealth." -Chad Womack, Senior Director, STEM Initiatives and Special Projects, UNCF.